Key Performance Indicators (Kpis) A Consultant’s Concern - P’ng, Suan Lin (Universiti Sains Malaysia, 2005)
This research is being conducted to investigate on the understanding of Key Performance Indicators in the Quantity Surveying Profession in construction industry. A brief explanation of Benchmarking is also being done as there are similar concepts toward the two tools. Furthermore comprehensive explanation has been done towards the use and application of Key Performance Indicators in the industry. The objective of this research is to introduce the significance of Key Performance Indicators to the profession by taking into consideration eight (8) chosen indicators. This research will be able to subdue on the usage and practise of Key Performance Indicators and how it help to increase the firm’s competitiveness in the industry.